Karnoprawne i administracyjnoprawne przepisy dotyczące reklamy produktów leczniczych - Olszewski, Bartosz; Hachoł, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
The article describes the issues of advertising of medicinal products, which is defined as an activity based on informative and encouraging actions towards a medicinal product that aims to increase: the number of prescriptions, supply, sales and consumption of medicinal products. The advertisement is controlled by both administrative and penal regulations. The main concern is to establish the legal regulation so that the penal regulation may be applied only when the application of administrative law would not be sufficient. It is also a principal matter because the Constitution of the Republic of Poland states as a rule that the freedom of economic activity can be restricted only when an important public interest exists. The article also elaborates on the issue of the substitution of penal regulation by administrative regulation and the associated risks to principal guarantees of a subject, which engages in the activity of advertising medicinal products.
Keywords: prawo farmaceutyczne; reklama produktów leczniczych; prawo karne; prawo administracyjne; odpowiedzialność za produkt